Academic Anxiety Among Higher Secondary School Students: Stream and Gender Differences - Nang Anusity Mannow; Alok Singh Yadav (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The present study is conducted in the light of finding out educational anxiety and educational achievement of secondary school students. It was hypothesized that there is a significant difference in gender among male and female secondary school students’ level of academic anxiety and academic achievement. For the verification of these hypotheses, the data was collected from 200 secondary school students of Namsai district of Arunachal Pradesh i.e. by adopting lottery method of random sampling by administrating ‘Academic Anxiety Scale by M. Abid Siddique and Atieq UI Rehman and their marks of class 9th to 12th were taken as Computational technique applied was t- test. According to the findings of the present study, it was found that there are significant differences in academic anxiety as well as academic achievement between male and female secondary school students. Girls were identified as more academically anxious and had great academic achievement than boys.